Pengaruh Orientasi Pembelajaran, Kemampuan Produksi, dan Orientasi Pasar Terhadap Strategi Bisnis dan Kinerja Bisnis - J.E. Sutanto (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2009)
One indicator of company’s or business’s successfulness in the competition was the company or business must have competitive advantage that allowed the industrial company of foods and beverages yielding the superiority of production result than their competitors in the determining the strategy and business performance continually. The population of this research was foods and beverages industry especially big and medium industrial company, which have multi-business and multi-products in the East Java area that consist of 1286 industrial companies of foods and beverages according to the Indonesian Business Field Classification (KLUI 15) years 2002. The data analysis technique used Structural Equation Modeling = SEM) with computer help used AMOS program 4.0 version.The research result indicated that: (1) all of independent variables have positive influence and significant toward the business strategy and the business performance; (2) simultaneously the influence of teaching orientation, production competence and market orientation toward business strategy and business performance was proper as the created model. The conclusion of this research was the research result generally indicated the existence of positive influence that experienced by that industrial company of foods and beverages both from test result partially or simultaneously. And that not all of partial or simultaneous influence toward business strategy and business performance has positive or negative result, but it still categorized as reasonable.